Craniofacial and Dental Manifestations of Melnick-Needles Syndrome: Literature Review and Orthodontic Management - Dorota Kustrzycka; Marcin Mikulewicz; Anna Pelc; Piotr Kosior; Maciej Dobrzyński (Hindawi Limited, 2018)
The aim of this article was to present a characteristic clinical image of Melnick-Needles syndrome using an example of an 11.5-year-old female patient treated at the Facial Congenital Disorders Outpatient Clinic as well as to present the actual literature review of the surgical treatment. The patient was diagnosed with several characteristics typical for Melnick-Needles syndrome: single-sided hearing loss, malocclusion, and facial dysmorphism, among others. Due to malocclusion and facial dysmorphism, the patient with Melnick-Needles syndrome requires orthodontic treatment with surgical intervention. Mandibular distraction with fixed appliance treatment is a recommended treatment protocol.